2017
DOI: 10.1371/journal.pone.0170879
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Programmed Death Ligand‑1 and Intra-Tumoral CD8+ T Lymphocytes in Ovarian Carcinosarcoma

Abstract: Ovarian carcinosarcoma (OCS) accounts for high mortality and lacks effective therapeutic methods. So far, we lack reliable biomarkers capable of predicting the risk of aggressive course of the disease. Programmed death ligand-1 (PD-L1) is expressed in various tumors, and antibodies targeting its receptor programmed cell death 1 (PD-1) are emerging cancer therapeutics. This study was designed to evaluate the expression of PD-L1 and intratumoral CD8+ T lymphocytes by immunohistochemistry from 19 OCS patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
1
26
1
9
Order By: Relevance
“…Although it was shown that PD-L1 expression was related with worse prognosis in tumors such as melanoma, non-small cell lung cancer (NSCLC), renal cell carcinoma (RCC), prostate cancer, and colorectal cancer, we found that PD-L1 expression was associated with better prognosis in UCS [5,6]. Similar to our study PDL-1 positivity has been found to be associated with good prognosis in ovarian carcinosarcoma [10]. By this time the prognostic effect of PD-L1 expression in ovarian cancer is controversial.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although it was shown that PD-L1 expression was related with worse prognosis in tumors such as melanoma, non-small cell lung cancer (NSCLC), renal cell carcinoma (RCC), prostate cancer, and colorectal cancer, we found that PD-L1 expression was associated with better prognosis in UCS [5,6]. Similar to our study PDL-1 positivity has been found to be associated with good prognosis in ovarian carcinosarcoma [10]. By this time the prognostic effect of PD-L1 expression in ovarian cancer is controversial.…”
Section: Discussionsupporting
confidence: 81%
“…Zu at al. revealed the negative impact of the mesenchymal PD-1 expression on survival [10]. Paydas at al.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Three comparisons included patients diagnosed with epithelial ovarian carcinoma (EOC), whereas remaining comparisons included patients with the subtypes of EOC: 8 comparisons included patients with HGSOC, 2 comparisons included patients with OCCC, 1 comparison included patients with ovarian carcinosarcoma (OCS). The HR with 95% CI was calculated according to the methods provided by Tierney et al in the study by Zhu et al [ 25 ] The studies by Hamanishi et al and by Xu et al provided the relative risk (RR) with 95% CI from Cox multifactor regression analysis using Cox hazard model, which were pooled with HRs together in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is essential to fully understand PD-L1 expression in NSCLC and the relationship between PD-L1 expression and prognosis. PD-L1 expression has been found in several cancers, including breast cancer 9 , lung cancer 10 , gastric cancer 11 , colorectal cancer 12 , ovarian cancer 13 , and prostate cancer 14 . Our previous study showed that positive PD-L1 expression was associated with poor prognosis in gastric cancer 15 , breast cancer 16 and surgical lung squamous cell carcinoma 17 .…”
Section: Introductionmentioning
confidence: 99%